Ruthenium-cobalt-loaded bimetallic core-shell structure nitrogen-doped porous carbon and preparation method and application thereof
By constructing a Co-containing MOFs core-shell structure, exposing Co elements and introducing Ru nanoparticles to form a ruthenium-doped porous carbon with nitrogen doped, the problems of poor performance of a single non-precious metal catalyst and excessive thickness of the MOF coating layer are solved, and the effect of efficient catalytic ammonia borane hydrolysis hydrogen reaction is achieved.
Patent Information
- Application Number
- CN202510013447.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-06
- Publication Date
- 2025-04-11
AI Technical Summary
In the prior art, the catalytic performance of a single non-precious metal catalyst is poor, and the coating layer formed by the MOF material during carbonization is too thick, resulting in a decrease in the diffusion rate of reactants and products.
Two Co-containing MOFs materials are used to construct the core-shell structure, expose the Co elements through calcination, and introduce trace amounts of Ru nanoparticles to form a ruthenium-doped porous carbon in the core-shell structure of ruthenium-doped porous carbon, achieving the synergistic effect between Ru and Co elements and improving catalytic performance.
The efficiency and selectivity of the catalytic reaction are significantly improved, the pore structure and specific surface area of the support are optimized, the diffusion rate of reactants and product release efficiency are improved, and the cycle stability is improved.
Smart Images

Figure CN119793481A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ammonia borane hydrolysis and hydrogenation in hydrogen storage materials, and in particular to nitrogen-doped porous carbon loaded with ruthenium-cobalt bimetallic core-shell structure, and a preparation method and application thereof. Background Art
[0002] Ammonia borane, with the molecular formula NH3BH3, referred to as AB, has the advantages of high theoretical hydrogen capacity, non-toxicity, environmental friendliness, and stability in solid state and room temperature environment. It is suitable for portable hydrogen supply system and can effectively solve the problem of hydrogen storage and transportation. However, ammonia borane has the problem of slow reaction kinetics of hydrolysis to produce hydrogen under room temperature conditions.
[0003] Metal-organic frameworks (MOFs) have high specific surface area, clear topological structure and good surface integrity, and can be used as catalytic materials for hydrogen production by hydrolysis of ammonia borane; however, the metal ions in MOFs are wrapped by ligands, which significantly reduces the exposure of active metal sites. Calcination treatment is used to remove some organic ligands in the material and convert the MOFs material into a porous carbon-nitrogen framework structure (CN), which not only retains the original pore structure of the MOF material, but also increases the exposure of metal particles, that is, increases the active sites. For example, the existing literature 1 (Fang M, Wu S, Chang Y, et al. Mechanistic insight into the synergetic interaction of ammonia borane and water on ZIF-67-derived Co@porous carbon for controlled generation of dihydrogen [J]. ACS Applied Materials & Interfaces, 2021, 13 (40): 47465-47477.) reported that ZIF-67-derived Co-loaded porous carbon nanoparticles (Co@PC) had a hydrogen evolution conversion rate of 13.2 mol in the catalytic hydrolysis and hydrogenation reaction of ammonia borane. H2 ·mol Co -1 ·min -1 This technical solution achieves the effect of exposing metal active sites through calcination, and promotes the activation of AB and the formation of Co-H intermediates through Co nanoparticles. However, the catalytic performance of this technical solution is still relatively low, because the catalytic performance is poor due to the use of a single non-precious metal as a catalyst.
[0004] In order to solve the problem of poor performance of single non-precious metal catalysts, trace amounts of precious metals can be introduced and combined with non-precious metals to form a composite catalyst. For example, in the existing literature 2 (Qu X, Yu Z, Li Z, et al. CoRh nanoparticles supported on ZIF-67 as highly efficient catalysts for hydrolytic dehydrogenation of ammonia boranes for chemical hydrogen storage [J]. International Journal of Hydrogen Energy, 2017, 42 (51): 30037-30043.), RhCo nanoparticles were anchored on ZIF-67 to prepare Rh 25 Co 75 @ZIF-67 catalytic material, in the catalytic hydrolysis and hydrogenation reaction of ammonia borane, the hydrogen evolution conversion rate is 100.21 mol H2 ·mol Rh -1 ·min -1 ; Moreover, the technical scheme is compared with Co@ZIF-67 and Rh@ZIF-67, proving that the performance improvement is attributed to the synergistic effect between Rh and Co, and that ZIF-67 has almost no catalytic activity, that is, the role in the technical scheme is to use the specific structure of ZIF-67 to achieve the dispersion of metal particles, that is, the technical scheme does not perform calcination and carbonization treatment on ZIF-67, and therefore, the Co metal in ZIF-67 is not exposed, which is consistent with the conclusion in the technical scheme that ZIF-67 has almost no catalytic activity, that is, the Co element in ZIF-67 has no direct contribution to the catalysis of ammonia borane hydrolysis.
[0005] In order to improve metal utilization, reduce raw material costs, and promote the synergistic performance between precious metals and non-precious metals, the metal particles in MOF materials can be directly used to form composite catalysts. For example, existing document 3 (Cui X, Li H, Yu G, et al. Pt coated Co nanoparticles supported on N-doped mesoporous carbon as highly efficient, magnetically recyclable and reusable catalyst for hydrogen generation from ammonia borane [J]. International Journal of Hydrogen Energy, 2017, 42 (44): 27055-27065.) uses a one-pot carbonization method to prepare Pt@Co / mCN catalytic materials with cobalt nanoparticles doped with fluffy nitrogen-doped mesoporous carbon (Co / mCN) anchoring Pt nanoparticles. In the catalytic hydrolysis and hydrogenation reaction of ammonia borane, the hydrogen evolution conversion rate is 118.25 mol H2 ·mol Rh -1 ·min -1 This technical solution utilizes the synergistic effect between CoNPs exposed on the surface of the Co / mCN carrier and Pt to improve the catalytic performance. However, although this technical solution utilizes the Co element in the carrier to achieve synergistic effect, it does not prepare MOF material as a carrier. Therefore, the obtained carrier has an irregular microstructure, that is, the specific structural characteristics of MOFs are not utilized. The impact of this problem on the technical effect is directly reflected in the small specific surface area of the obtained material, which is only 90.1m 2 ·g -1 Moreover, the average pore size is relatively large, reaching 9.3 nm, which results in the inability to effectively improve the dispersion when Pt is subsequently loaded.
[0006] In order to obtain the effect of forming specific morphological features and exposing metal active sites, non-precious metal MOFs materials with regular morphology can be used, and then converted into cobalt-nitrogen-doped porous carbon as a carrier through a carbonization process, and finally combined with precious metal nanoparticles to form a synergistic catalytic system, which can achieve the technical effect of improving catalytic activity. For example, the existing document 4 (Cui B, Wu G, Qiu S, et al. Ruthenium supported on cobalt-embedded porous carbon with hollow structure as efficient catalysts toward ammonia-boranehydrolysis for hydrogen production [J]. Advanced Sustainable Systems, 2021, 5 (10): 2100209.) is the preliminary research result of the research group of the inventor of the present invention. The core-shell structured ZIF-8@ZIF-67 composite material is carbonized in one step to obtain a cobalt-embedded porous carbon CoPCP with a polyhedral structure. Subsequently, Ru nanoparticles are loaded on CoPCP by in-situ reduction to obtain a Ru / CoPCP catalyst with a hollow structure. In the catalytic hydrolysis and hydrogenation of ammonia borane, the hydrogen evolution conversion rate is 243.4 mol H2 ·mol Ru -1 ·min -1 , and the activation energy is low E a =31.25 kJ·mol -1 This technical solution effectively inhibits the agglomeration of Ru nanoparticles through the hollow structure of CoPCP, and realizes the synergistic effect between Co and Ru in the carrier. However, subsequent studies have found that this technical solution still has the following technical problems: the specific surface area of the CoPCP carrier is small, only 140.3m 2 ·g -1 , and the catalytic efficiency is low. The reason is that the use of ZIF-67 as the raw material of the coating layer causes the thickness of Co-NC to reach 108nm, which directly leads to a reduction in the diffusion rate of reactants and products on the catalyst surface. The reason for this problem is that the microstructure of ZIF-67 is a rhombic dodecahedron structure, that is, it has a specific microstructure, which causes the thickness of the formed Co-NC coating layer to be too thick. Summary of the invention
[0007] The purpose of the present invention is to provide a nitrogen-doped porous carbon with a ruthenium-cobalt bimetallic core-shell structure and a preparation method and application thereof. In view of the technical problems existing in the prior art, the basic principle of the present invention to solve the problems of the prior art is: using two Co-containing MOFs materials to construct a core-shell structure, then exposing the Co element in the carrier by calcination, and finally introducing a trace amount of Ru nanoparticles as key active sites, and finally, through the synergistic effect between Ru and Co elements, a technical effect of significantly improving the catalytic performance is achieved.
[0008] The specific technical features involved include:
[0009] 1. Carbonization of MOFs materials is used to increase the exposure of Co metal in the carrier, promote the synergistic effect between Co and the introduced Ru metal, and improve the efficiency and selectivity of the catalytic reaction;
[0010] 2. Calcination treatment optimizes the pore structure and specific surface area of the carrier, which is conducive to the rapid diffusion of reactants and the effective release of products, further optimizes the catalytic process and improves the overall catalytic performance;
[0011] 3. The core-shell structure protects Ru nanoparticles, effectively inhibits the agglomeration of Ru nanoparticles during the catalytic process, and improves the cycle stability.
[0012] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention is:
[0013] A ruthenium-cobalt bimetallic core-shell structure nitrogen-doped porous carbon RuCo-NC-1 / NC-2, which is composed of cobalt-cobalt core-shell structure nitrogen-doped porous carbon Co-NC-1 / NC-2 and Ru nanoparticles, wherein the nitrogen source of the RuCo-NC-1 / NC-2 is dimethylimidazole and terephthalic acid organic ligands, the cobalt source is hexahydrated cobalt nitrate, and the ruthenium source is ruthenium trichloride hydrate; wherein,
[0014] The Co-NC-1 / NC-2 is prepared by calcining ZIF-67 / MOF-74 at high temperature, wherein the Co metal ions are reduced in a hydrogen-argon mixed gas calcination atmosphere;
[0015] The ZIF-67 / MOF-74 is obtained by chemical synthesis using cobalt nitrate hexahydrate, dimethylimidazole and terephthalic acid organic ligand as raw materials;
[0016] The ruthenium nanoparticles are obtained by reducing ruthenium trichloride hydrate with ammonia borane;
[0017] ZIF-67 has a rhombic dodecahedral structure and a size of 0.88 μm;
[0018] ZIF-67 / MOF-74 presents a rough-surfaced rhombic dodecahedron structure with a size of 1.15 μm;
[0019] Co-NC-1 / NC-2 presents an inwardly concave rhombic dodecahedron structure with a size of 1.05 μm and a coating layer thickness of 42 nm;
[0020] RuCo-NC-1 / NC-2 presents an inwardly concave rhombic dodecahedron structure with a size of 1.05 μm and a coating thickness of 42 nm;
[0021] Ru nanoparticles are loaded in the internal pores of Co-NC-1 / NC-2.
[0022] A method for preparing nitrogen-doped porous carbon loaded with a ruthenium-cobalt bimetallic core-shell structure comprises the following steps:
[0023] Step 1, preparation of ZIF-67, first, under certain conditions, cobalt nitrate hexahydrate is placed in methanol for ultrasonication to obtain solution A; at the same time, dimethylimidazole is placed in methanol to obtain solution B; then, under magnetic stirring conditions, solution B is slowly added dropwise to solution A and mixed evenly to obtain solution C; then, at room temperature, solution C is reacted under conditions of ultrasonication followed by stirring; after the reaction is completed, the purple precipitate obtained by the reaction is centrifuged and washed under certain conditions; finally, it is dried under certain conditions to obtain purple precipitate ZIF-67;
[0024] In the step 1, the molar ratio of cobalt nitrate hexahydrate to dimethylimidazole is 1:4;
[0025] In the step 1, the ultrasonic condition for preparing solution A is that the ultrasonic time is 5-10 min;
[0026] In step 1, the conditions of ultrasonication followed by stirring are as follows: the ultrasonication time is 5-10 min, and the stirring time is 4-6 h;
[0027] In step 1, the centrifugal washing conditions are: methanol is used as the washing liquid, and the centrifugal speed is 6000-8000 r·min -1 , the centrifugation time is 3-5min, the washing times are 3-5 times; the drying conditions are: the drying temperature is 60-80℃, and the drying time is 10-12h;
[0028] Step 2, preparation of ZIF-67 / MOF-74, first, ZIF-67, cobalt nitrate hexahydrate and terephthalic acid obtained in step 1 are placed in a DMF solution and mixed to obtain a solution D, then, under certain conditions, the solution D is subjected to a hydrothermal reaction, after the reaction is completed, the precipitate obtained by the reaction is centrifuged and washed under certain conditions; finally, it is dried under certain conditions to obtain a dark red precipitate ZIF-67 / MOF-74;
[0029] In the step 2, the mass ratio of ZIF-67, cobalt nitrate hexahydrate, and terephthalic acid is 10:3:1;
[0030] In step 2, the conditions of the hydrothermal reaction are: the hydrothermal temperature is 100-120° C., and the hydrothermal time is 3-5 h;
[0031] In step 2, the centrifugal washing conditions are: ethanol as the washing liquid, and the centrifugal speed is 6000-8000 r·min -1 , the centrifugation time is 3-5min, the washing times are 3-5 times; the drying conditions are: the drying temperature is 60-80℃, and the drying time is 10-12h;
[0032] Step 3, preparation of Co-NC-1 / NC-2, calcining the ZIF-67 / MOF-74 obtained in step 2 under certain conditions to obtain nitrogen-doped porous carbon Co-NC-1 / NC-2 with a cobalt core-shell structure;
[0033] In step 3, the calcination conditions are: argon-hydrogen mixed atmosphere, heating rate 3-5°C·min -1 , calcination temperature 450-650℃, calcination time 2-4h;
[0034] Step 4, preparation of RuCo-NC-1 / NC-2, first, Co-NC-1 / NC-2 and ruthenium trichloride hydrate satisfy a certain mass ratio, Co-NC-1 / NC-2 is placed in deionized water to obtain solution E, and at the same time, ruthenium trichloride hydrate is placed in deionized water to obtain solution F, then, under magnetic stirring conditions, solution F is slowly added dropwise to solution E to mix evenly to obtain solution G, and then solution G is reacted at room temperature under the conditions of first ultrasound and then stirring. After the reaction is completed, deionized water is used as a washing liquid, and the purple precipitate obtained by the reaction is filtered and washed, and finally, it is dried under certain conditions to obtain a black product loaded with ruthenium cobalt bimetallic core-shell structure nitrogen-doped porous carbon RuCo-NC-1 / NC-2;
[0035] In the step 4, the mass ratio of Co-NC-1 / NC-2 to ruthenium trichloride hydrate is 10:3;
[0036] In step 4, the conditions of ultrasonication followed by stirring are as follows: the ultrasonication time is 20-40 min, and the stirring time is 20-30 min;
[0037] In step 4, the drying conditions are as follows: the drying temperature is 60-80° C. and the drying time is 10-12 hours.
[0038] When the ruthenium-cobalt bimetallic core-shell structure nitrogen-doped porous carbon is used as a catalyst for the hydrolysis and hydrogenation of ammonia borane, the hydrolysis rate is 98-100% at 25°C, the time for complete hydrogenation is 15-40s, and the maximum hydrogen evolution conversion rate is 400-450mol H2 ·mol Ru -1 ·min -1 ; The activation energy of catalytic hydrogen release is E a =25-30 kJ·mol -1 When the number of cycles is 10, the hydrolysis rate remains at 100%. When the number of cycles is 5, the time for complete hydrogen release is 50s, and the maximum hydrogen evolution conversion rate is 365.8mol H2 ·mol Ru -1 ·min -1 The maximum hydrogen evolution conversion rate was maintained at 89.5%; when the number of cycles was 10, the time for complete hydrogen release was 68s, and the maximum hydrogen evolution conversion rate was 289.9mol H2 ·mol Ru -1 ·min -1 , the retention rate of the maximum hydrogen evolution conversion rate is 70.9%.
[0039] The beneficial technical effects of the material obtained by the present invention can be seen from the following tests:
[0040] XRD detection of the present invention shows that RuCo-NC-1 / NC-2 contains characteristic peaks of Co and Ru metal elements in addition to the characteristic peaks of C. The test results show that Co metal ions are reduced and Ru metal particles are introduced;
[0041] The EDS test of the present invention shows that RuCo-NC-1 / NC-2 contains not only C, N, O and Co elements, but also Ru elements, and the element distribution positions are relatively concentrated;
[0042] The present invention is tested by SEM and found that: RuCo-NC-1 / NC-2 presents an inwardly concave rhombic dodecahedron structure with a size of 1.05 μm;
[0043] The present invention has been tested for hydrogen production and found that: under the condition of 25°C, the hydrolysis rate is 98-100%, the time for complete hydrogen release is 15-40s, and the maximum hydrogen evolution conversion rate is 400-450mol H2 ·mol Ru -1 ·min -1 ;
[0044] The present invention has been tested for reaction kinetics and found that the apparent activation energy E of the reaction is a=25-30 kJ·mol -1 ;
[0045] The present invention has been tested for cycle performance. It is known that at 25°C, after 10 cycles, the hydrolysis rate remains at 100%, the time for complete hydrogen release is 60-70s, and the maximum hydrogen evolution conversion rate is 280-320mol H2 ·mol Ru -1 ·min -1 , the catalyst retains 65%-75% of its initial catalytic activity.
[0046] Therefore, the present invention has the following advantages over the prior art:
[0047] 1. Use two MOFs materials (ZIF-67 and MOF-74) to construct a MOFs-on-MOFs core-shell structure. ZIF-67 has a high specific surface area and large porosity as a carrier; MOF-74 has a highly ordered hexagonal pore structure and unsaturated metal sites, which are conducive to the adsorption and diffusion of gas molecules. The MOFs-on-MOFs structure is used to form a composite material with a synergistic effect.
[0048] 2. The MOFs composite material was carbonized by hydrogen-argon mixed gas to obtain nitrogen-doped porous carbon with cobalt core-shell structure. This process not only increased the exposure of Co metal, but also improved the electron transfer efficiency, thereby enhancing the catalytic performance.
[0049] 3. Loading Ru nanoparticles into the internal pores of Co-NC-1 / NC-2 effectively improves the dispersion and active site exposure of Ru. At the same time, NC-2 effectively inhibits the agglomeration of Ru during the cycle, prevents the Ru nanoparticles from falling off, and improves the cycle stability.
[0050] 4. The Co element in MOFs regulates the electronic structure of Ru, increases the intrinsic activity of Ru nanoparticles, and further improves the catalytic performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0051] Figure 1 XRD patterns of ZIF-67, MOF-74, and ZIF-67 / MOF-74 prepared in Example 1;
[0052] Figure 2 This is a SEM image of ZIF-67 prepared in step 1 of Example 1;
[0053] Figure 3 This is the SEM image of ZIF-67 / MOF-74 prepared in step 2 of Example 1;
[0054] Figure 4XRD patterns of Co-NC-1 / NC-2 and RuCo-NC-1 / NC-2 prepared in Example 1;
[0055] Figure 5 This is the EDS image of Co-NC-1 / NC-2 prepared in step 3 of Example 1;
[0056] Figure 6 This is the SEM image of Co-NC-1 / NC-2 prepared in step 3 of Example 1;
[0057] Figure 7 TEM image of Co-NC-1 / NC-2 prepared in step 3 of Example 1;
[0058] Figure 8 Specific surface area diagram of Co-NC-1 / NC-2 prepared in step 3 of Example 1 and Comparative Example 1;
[0059] Fig. 9 The curve of Co-NC-1 / NC-2 prepared in step 3 of Example 1 catalyzing the hydrolysis and hydrogenation of ammonia borane at 25°C;
[0060] Fig.10 This is the EDS image of RuCo-NC-1 / NC-2 prepared in step 4 of Example 1;
[0061] Fig.11 This is a SEM image of RuCo-NC-1 / NC-2 prepared in step 4 of Example 1;
[0062] Fig.12 TEM image and high-resolution transmission electron microscopy image of RuCo-NC-1 / NC-2 prepared in step 4 of Example 1;
[0063] Fig.13 The hydrolysis and hydrogenation curves of ammonia borane catalyzed by RuCo-NC-1 / NC-2 prepared in Example 1 and Comparative Examples 1 and 2;
[0064] Fig.14 It is a summary diagram of the conversion rate of hydrogen evolution catalyzed by ammonia borane hydrolysis and hydrogen release by RuCo-NC-1 / NC-2 prepared in Example 1 and Comparative Examples 1 and 2;
[0065] Fig.15 The hydrolysis and hydrogenation curves of ammonia borane catalyzed by RuCo-NC-1 / NC-2 at different temperatures in Example 1;
[0066] Fig.16 The summary of the conversion rate of hydrogen evolution by ammonia borane hydrolysis catalyzed by RuCo-NC-1 / NC-2 at different temperatures and the activation energy curve in Example 1;
[0067] Fig.17 This is a test curve of 10 cycles of RuCo-NC-1 / NC-2 catalyzing hydrolysis and hydrogenation of ammonia borane in Example 1;
[0068] Fig.18 A summary diagram of the hydrogen evolution conversion rate and cycle retention rate of 10 cycles of RuCo-NC-1 / NC-2 catalyzing ammonia borane hydrolysis and hydrogenation in Example 1;
[0069] Fig.19 The curve diagram of the 5-cycle test of catalytic hydrolysis of ammonia borane and the hydrogen evolution conversion rate and cycle retention rate of Comparative Example 1;
[0070] Fig. 20 This is a test curve of 5 cycles of catalytic hydrolysis of ammonia borane for comparative example 2, as well as the hydrogen evolution conversion rate and cycle retention rate. DETAILED DESCRIPTION
[0071] The present invention is further described in detail through Example 1 in conjunction with the accompanying drawings, but the present invention is not limited thereto.
[0072] Example 1
[0073] A method for preparing nitrogen-doped porous carbon loaded with a ruthenium-cobalt bimetallic core-shell structure comprises the following steps:
[0074] Step 1, preparation of ZIF-67, first, with an ultrasonic time of 5 minutes, 291 mg of cobalt nitrate hexahydrate is placed in 80 mL of methanol for ultrasonication to obtain solution A; at the same time, 328.4 mg of dimethylimidazole is placed in 20 mL of methanol to obtain solution B; then, under magnetic stirring conditions, solution B is slowly added dropwise to solution A and mixed evenly to obtain solution C; then, at room temperature, solution C is reacted under the conditions of ultrasonication first and then stirring; after the reaction is completed, methanol is used as a washing liquid, and the centrifugal speed is 8000 r·min -1 , centrifugation time is 3min, washing times are 3 times, the purple precipitate obtained by the reaction is centrifuged and washed; finally, drying is performed at a drying temperature of 60°C and a drying time of 12h to obtain a purple precipitate, which is named ZIF-67;
[0075] In step 1, the conditions of ultrasonication followed by stirring are as follows: the ultrasonication time is 5 min and the stirring time is 4 h.
[0076] In order to prove the phase composition of ZIF-67 obtained in step 1, XRD test was performed. The test results are as follows Figure 1 As shown, the characteristic peaks of ZIF-67 are consistent with those of standard ZIF-67. At the same time, the strong and sharp diffraction peaks indicate that ZIF-67 has high crystallinity.
[0077] In order to verify the microstructure of ZIF-67 obtained in step 1, SEM test was performed. The test results are shown in Figure 2 As shown, the microstructure of ZIF-67 is a rhombic dodecahedron structure with a size of 0.88 μm, and the surface of ZIF-67 is smooth.
[0078] Step 2, preparation of ZIF-67 / MOF-74, first, 500 mg of ZIF-67 obtained in step 1, 150 mg of cobalt nitrate hexahydrate, and 50 mg of terephthalic acid were placed in 30 mL of DMF solution and mixed to obtain solution D, then, solution D was subjected to hydrothermal reaction at a hydrothermal temperature of 100 ° C and a hydrothermal time of 3 h. After the reaction was completed, ethanol was used as a washing liquid and the centrifugal speed was 8000 r·min -1 , the centrifugal time is 3 min, and the number of washing times is 3 times, the precipitate obtained by the reaction is centrifuged and washed; finally, it is dried at a drying temperature of 60 ° C and a drying time of 8 h to obtain a dark red precipitate, which is named ZIF-67 / MOF-74;
[0079] In order to prove the phase composition of ZIF-67 / MOF-74 obtained in step 2, that is, to prove the effect of step 2, XRD test was carried out. The test results are as follows Figure 1 As shown, ZIF-67 / MOF-74 only contains the characteristic peaks of ZIF-67, and the intensity of the original ZIF-67 diffraction peak is reduced. The test results show that,
[0080] The presence of only the characteristic peaks of ZIF-67 indicates that step 2 did not change or destroy the crystal structure of ZIF-67, that is, ZIF-67 maintained a complete and stable crystal structure;
[0081] Further combined with the decrease in the diffraction peak intensity, it shows that the MOF-74 prepared in step 2 only forms a coating layer on the surface of ZIF-67, that is, the coating is successful.
[0082] In order to prove the microscopic morphology of ZIF-67 / MOF-74 obtained in step 2, that is, to prove the effect of step 2, SEM test was carried out. The test results are as follows Figure 3 As shown, the microstructure of ZIF-67 / MOF-74 still maintains a rhombic dodecahedron structure with a size of 1.15 μm. However, the surface of ZIF-67 / MOF-74 is rough, and there are uniformly raised small particles. Combined with the XRD test results, it can be seen that the small particles on the surface of ZIF-67 / MOF-74 are MOF-74. The test results show that step 2 forms a coating layer of MOF-74 on the surface of ZIF-67 while maintaining the rhombic dodecahedron structure of ZIF-67. At the same time, due to the formation of the coating layer, the size increases from 0.88 μm to 1.15 μm.
[0083] Step 3, preparation of Co-NC-1 / NC-2, in an argon-hydrogen mixed atmosphere, with a heating rate of 3 °C min -1 The ZIF-67 / MOF-74 obtained in step 2 was calcined at 550°C for 3 h to obtain nitrogen-doped porous carbon with a cobalt core-shell structure, named Co-NC-1 / NC-2.
[0084] In order to prove the phase composition of Co-NC-1 / NC-2 obtained in step 3, that is, to prove the effect of step 3, XRD test was carried out. The test results are as follows Figure 4 As shown, Co-NC-1 / NC-2 contains both the characteristic peaks of C and the characteristic peaks of Co metal, while the characteristic peaks of ZIF-67 disappear. The test results show that the organic ligands in ZIF-67 / MOF-74 decompose to form carbon materials, and the central metal Co element is exposed and reduced to metal.
[0085] In order to further prove the composition of Co-NC-1 / NC-2 obtained in step 3, EDS test was performed. The test results are as follows Figure 5 As shown, Co-NC-1 / NC-2 contains C element, N element, O element and Co element at the same time, and each element is evenly distributed.
[0086] In order to verify the microstructure of Co-NC-1 / NC-2 obtained in step 3, SEM test was performed. The test results are shown in Figure 6 As shown in the figure, the microstructure of Co-NC-1 / NC-2 still maintains a rhombic dodecahedron structure with a size of 1.05μm, but the surface of Co-NC-1 / NC-2 is concave inward. The test results show that while step 3 carbonizes the organic ligands by calcination, the rhombic dodecahedron structure of ZIF-67 / MOF-74 can still be maintained. At the same time, due to carbonization, the size is slightly reduced from 1.15μm to 1.05μm.
[0087] In order to further verify the microstructure of Co-NC-1 / NC-2 obtained in step 3, TEM test was performed. The test results are shown in Figure 7 As shown, the microstructure of Co-NC-1 / NC-2 is a rhombic dodecahedron structure, showing an obvious core-shell structure, and the thickness of the coating layer is 42 nm.
[0088] In order to prove the pore structure characteristics of Co-NC-1 / NC-2 obtained in step 3, BET test was performed. The test results are shown in Figure 8 As shown in Figure 2, the specific surface area of Co-NC-1 / NC-2 is 1702.8 m 2 ·g -1 .
[0089] In order to prove the performance of Co-NC-1 / NC-2 as a catalyst for the hydrolysis and hydrogenation of ammonia borane, that is, to compare it with the subsequent RuCo-NC-1 / NC-2, a catalytic hydrolysis and hydrogenation performance test of ammonia borane was carried out, referred to as the hydrogen production test. The specific method of the hydrogen production test is as follows: first, under standard atmospheric pressure and 25°C, 20 mg of the sample to be tested is placed in a wide-mouth bottle, 20 mL of deionized water is added and stirred and dispersed, then the wide-mouth bottle is connected to a metering tube filled with water in a constant temperature water bath, and 10 mL of 0.1 mmol·mL is injected under magnetic stirring conditions. -1 of ammonia borane aqueous solution, and finally, calculate the volume of generated hydrogen by the water displacement method; wherein, the hydrogen evolution conversion rate is calculated by the hydrogen release time, which can reflect the reaction rate of hydrolysis and hydrogen release.
[0090] The hydrogen production test results of Co-NC-1 / NC-2 are as follows Fig. 9 As shown in the figure, after the catalytic time reaches 180s, the volume of released hydrogen is 2mL. The test results show that the catalytic performance of Co-NC-1 / NC-2 is negligible.
[0091] Step 4, preparation of RuCo-NC-1 / NC-2, first, with a mass ratio of Co-NC-1 / NC-2 to ruthenium trichloride hydrate of 10:3, 20 mg of Co-NC-1 / NC-2 was placed in 10 mL of deionized water to obtain solution E, and at the same time, 6 mg of ruthenium trichloride hydrate was placed in 10 mL of deionized water to obtain solution F, then, under magnetic stirring conditions, solution F was slowly added dropwise to solution E and mixed evenly to obtain solution G, and then solution G was reacted at room temperature under the conditions of first ultrasound and then stirring. After the reaction was completed, deionized water was used as a washing liquid, and the purple precipitate obtained by the reaction was filtered and washed, and finally, it was dried at a drying temperature of 60°C and a drying time of 12 h to obtain a black product loaded with ruthenium cobalt bimetallic core-shell structure nitrogen-doped porous carbon, referred to as RuCo-NC-1 / NC-2;
[0092] In step 4, the conditions of ultrasonication followed by stirring are as follows: the ultrasonication time is 20 min and the stirring time is 30 min.
[0093] In order to prove the phase composition of RuCo-NC-1 / NC-2 obtained in step 4, XRD test was carried out. The test results are shown in Figure 4 As shown in Figure 2, RuCo-NC-1 / NC-2 contains the characteristic peaks of Ru metal element in addition to the characteristic peaks of C and Co metal element. The test results show that step 3 successfully introduced the Ru element.
[0094] In order to further prove the composition of RuCo-NC-1 / NC-2 obtained in step 4, EDS test was performed. The test results are as follows Fig.10As shown, RuCo-NC-1 / NC-2 contains Ru element in addition to C element, N element, O element and Co element, and the element distribution is uniform. The EDS test results are consistent with the XRD test results, indicating that the Ru element is successfully loaded.
[0095] In order to verify the microstructure of RuCo-NC-1 / NC-2 obtained in step 4, SEM test was performed. The test results are shown in Fig.11 As shown, RuCo-NC-1 / NC-2 still maintains a rhombic dodecahedron structure with a size of 1.05 μm, which is consistent with the morphology of Co-NC-1 / NC-2 obtained in step 3, without obvious changes. The test results show that loading Ru elements in step 4 does not affect the microscopic morphology, that is, Ru nanoparticles are loaded in the internal pores of Co-NC-1 / NC-2.
[0096] In order to further verify the microstructure of RuCo-NC-1 / NC-2 obtained in step 4, TEM test was performed. The test results are shown in Fig.12 As shown in A, RuCo-NC-1 / NC-2 still maintains a rhombic dodecahedron structure, which is consistent with the morphology of Co-NC-1 / NC-2 obtained in step 3, with no obvious change; further HRTEM test results are shown in Fig.12 As shown in B, there is an obvious core-shell structure interface between RuCo-NC-1 and NC-2. The test results show that loading Ru element in step 4 does not change the core-shell structure of the material.
[0097] In order to prove the performance of RuCo-NC-1 / NC-2 as a catalyst for the hydrolysis and hydrogenation reaction of ammonia borane, a hydrogen production test was carried out. The test results are shown in Fig.13 and Fig.14 As shown, under the condition of 25℃, the hydrolysis rate is 100%, the time for complete hydrogen release is 42s, and the maximum hydrogen evolution conversion rate is 408.9mol H2 ·mol Ru -1 ·min -1 . Compared with Co-NC-1 / NC-2 obtained in step 3, it can be seen that the introduction of Ru atoms can significantly improve the catalytic hydrogen production performance, which proves the role of the Ru element. The reason is that Ru, as the main catalytic active site, is embedded in the sandwich layer of Co-NC-1 / NC-2, which can produce a synergistic effect with Co atoms, accelerate the electron transfer rate, and significantly improve the hydrolysis hydrogenation rate; at the same time, compared with the existing document 4, it can be seen that the catalytic performance of the present invention is better than the prior art, with an improvement of 1.6 times.
[0098] In order to demonstrate the effect of RuCo-NC-1 / NC-2 on the hydrolysis kinetics of ammonia borane, hydrogen production tests were carried out at different temperatures. The specific test temperatures were 25, 35, 45, and 55°C. The test results are shown in Figure 2. Fig.15 As shown in Table 1, as the temperature increases, the rate of hydrogen release increases significantly. The results of the activation energy calculated by fitting the Arrhenius equation are as follows: Fig.16 As shown, the apparent activation energy of the RuCo-NC-1 / NC-2 reaction is E a =28.43 kJ·mol -1 The fitting results show that RuCo-NC-1 / NC-2 can significantly improve the kinetics of ammonia borane hydrolysis reaction.
[0099] Table 1 Hydrogen evolution conversion corresponding to the hydrolysis of ammonia borane catalyzed by RuCo-NC-1 / NC-2 at different temperatures
[0100] Temperature(℃) 25 35 45 55 <![CDATA[Hydrogen evolution conversion rate (mol H2 ·mol Ru -1 ·min -1 )]]> 408.9 648.5 902.1 1171.6
[0101] In order to prove the cycle performance of RuCo-NC-1 / NC-2, a cycle performance test was conducted. The specific test method is: repeatedly injecting an equal amount of ammonia borane aqueous solution to perform a hydrogen production test to achieve the cycle performance test. The test results are as follows Fig.17 , Fig.18 As shown in Table 2, at 25°C,
[0102] When the number of cycles is 5, the time for complete hydrogen release is 50s, and the maximum hydrogen evolution conversion rate is 365.8mol H2 ·mol Ru -1 ·min -1 , the maximum hydrogen evolution conversion rate was maintained at 89.5%;
[0103] When the number of cycles is 10, the time for complete hydrogen release is 68s, and the maximum hydrogen evolution conversion rate is 289.9mol H2 ·mol Ru -1 ·min -1 , the retention rate of the maximum hydrogen evolution conversion rate is 70.9%.
[0104] Table 2 Summary of cycle retention rates of RuCo-NC-1 / NC-2
[0105] Cycle times 1 2 3 4 5 6 7 8 9 10 Cycle retention rate / % 100 95.2 39.6 91.2 89.5 85.6 85.2 76.4 75.7 70.9
[0106] In order to demonstrate the influence of NC-1 and NC-2 on the catalytic performance of RuCo-NC-1 / NC-2, that is, the role of ZIF-67 and MOF-74 in the technical solution, Comparative Examples 1 and 2 are provided, which are ruthenium-based catalytic materials prepared without introducing MOF-74 and without introducing ZIF-67, respectively.
[0107] Comparative Example 1
[0108] A ruthenium-based catalytic material without introducing ZIF-67, the steps not specifically described in the specific steps are the same as those in Example 1, except that: step 1 is not required, and in step 2, ZIF-67 is not added to solution D, and the obtained material is named RuCo-NC-2.
[0109] The hydrogen production test results of RuCo-NC-2 are as follows Fig.13 and Fig.14 As shown, under the condition of 25℃, the hydrolysis rate is 100%, the time for complete hydrogen release is 183s, and the maximum hydrogen evolution conversion rate is 96.0mol H2 ·mol Ru -1 ·min -1 By comparing RuCo-NC-2 with RuCo-NC-1 / NC-2 of Example 1, it can be seen that the introduction of ZIF-67 can significantly improve the catalytic hydrogen production performance of RuCo-NC-2, with an improvement of 425%. The reason is that the introduction of ZIF-67 can form NC-1 / NC-2 with a core-shell structure, which can effectively improve the dispersibility of Ru nanoparticles when loading Ru nanoparticles, and at the same time, increase the exposure area of Ru nanoparticles, that is, increase the catalytic active sites.
[0110] In order to prove the cycle performance of RuCo-NC-2, a cycle performance test was carried out. The test results are shown in Fig.19 As shown in Table 3, under the condition of 25°C, when the number of cycles is 5, the theoretical hydrogen release capacity cannot be reached, and the maximum hydrogen evolution conversion rate is 24.7 mol H2 ·mol Ru -1 ·min -1 , the retention rate of the maximum hydrogen evolution conversion rate is 36.2%.
[0111] By comparing RuCo-NC-2 with RuCo-NC-1 / NC-2 of Example 1, it can be seen that the introduction of ZIF-67 can significantly improve the cycle stability of catalytic hydrogen production by 247%. The reason is that since ZIF-67 has a three-dimensional structure and structural stability, when MOF-74 is further coated on the surface of ZIF-67, the complexity and stability of the structure can be further increased to form a core-shell structure, and then when NC-1 / NC-2 is formed by calcination, the core-shell structure characteristics can be retained, and finally, the dispersibility of Ru nanoparticles is improved.
[0112] Table 3 Summary of cycle retention rate of RuCo-NC-2
[0113] Cycle times 1 2 3 4 5 Cycle retention rate / % 100 97.1 85.0 52.2 36.2
[0114] Comparative Example 2
[0115] A ruthenium-based catalytic material without introducing MOF-74, wherein the steps not particularly described in the specific steps are the same as those in Example 1, except that: step 2 is not required, and in step 3, the ZIF-67 obtained in step 1 is used instead of ZIF-67 / MOF-74, wherein the material obtained in step 3 is named Co-NC-1, and the material obtained in step 4 is named RuCo-NC-1.
[0116] In order to prove the effect of MOF-74 coating in step 2, the pore structure characteristics of Co-NC-1 obtained in step 3 were tested by BET test. Figure 7 As shown, the specific surface area of Co-NC-1 is 1268.1 m 2 ·g -1 .
[0117] By comparing Co-NC-1 with Co-NC-1 / NC-2 in Example 1, it can be seen that the introduction of MOF-74 can significantly increase the specific surface area. The reason is that MOF-74 has a hollow structure characteristic of hexagonal channels, so it has a high specific surface area. After calcination treatment on this basis, it can still maintain the original pore structure, thereby achieving a significant increase in the specific surface area when NC-2 is used as the coating layer.
[0118] The hydrogen production test results of RuCo-NC-1 are as follows Fig.13 and Fig.14 As shown, under the condition of 25℃, the hydrolysis rate is 100%, the time for complete hydrogen release is 59s, and the maximum hydrogen evolution conversion rate is 302.2mol H2 ·mol Ru -1 ·min -1 By comparing RuCo-NC-1 with RuCo-NC-1 / NC-2 of Example 1 and RuCo-NC-2 of Comparative Example 1, it can be seen that although the introduction of MOF-74 does not improve the catalytic hydrogen production performance as much as the introduction of ZIF-67, the improvement is still 135%. The reason is that the introduction of MOF-74 can form a core-shell structure, increase the specific surface area and porosity of Co-NC-1 / NC-2, and provide more anchoring sites for Ru, that is, increase the catalytic active sites.
[0119] In order to prove the cycle performance of RuCo-NC-1, a cycle performance test was carried out. The test results are shown in Fig. 20 As shown in Table 4, under the condition of 25°C temperature, when the number of cycles is 5, the time for complete hydrogen release is 91s, and the maximum hydrogen evolution conversion rate is 199.5 mol H2 ·mol Ru -1 ·min -1, the retention rate of the maximum hydrogen evolution conversion rate is 66.0%.
[0120] By comparing RuCo-NC-1 with RuCo-NC-1 / NC-2 of Example 1 and RuCo-NC-2 of Comparative Example 1, it can be seen that although the effect of introducing MOF-74 on improving the cycle stability is not as good as that of introducing ZIF-67, the improvement has also reached 135.6%. The reason is that since MOF-74 has the characteristics of hexagonal hollow channel structure, large specific surface area and high porosity, when MOF-74 is further coated on the surface of ZIF-67, a core-shell structure can be formed, which effectively increases the specific surface area and porosity of the overall material, and when NC-1 / NC-2 is formed by subsequent calcination, the core-shell structure characteristics can be retained, and finally, the agglomeration phenomenon of Ru in the cycle process is solved, and the cycle stability is further improved.
[0121] Table 4 Summary of cycle retention rate of RuCo-NC-1
[0122] Cycle times 1 2 3 4 5 Cycle retention rate / % 100 93.9 92.9 73.0 66.0
[0123] By comparing Comparative Example 1 and Comparative Example 2 with Example 1, it can be seen that RuCo-NC-1 / NC-2 combines the advantages of two MOFs materials and core-shell structure, thereby achieving a synergistic effect, which is specifically reflected in:
[0124] 1. Co-NC-1 has a three-dimensional structure of rhombic dodecahedron. As the core layer, Ru nanoparticles are dispersed on the surface of the carrier, which can enhance the dispersibility of Ru nanoparticles. However, the single use has the problem of poor anchoring effect on Ru nanoparticles and is prone to agglomeration.
[0125] 2. Co-NC-2 has a hexagonal channel hollow structure. As a shell layer, it can increase the anchoring points of Ru nanoparticles and effectively inhibit cyclic agglomeration. At the same time, it ensures the smooth entry of reactant water molecules and ammonia borane molecules. However, the single use has the problem of easy collapse of the hollow structure, making it difficult to achieve the theoretical hydrogen release capacity of ammonia borane hydrolysis.
Claims
1. A nitrogen-doped porous carbon RuCo-NC-1 / NC-2 loaded with a ruthenium-cobalt bimetallic core-shell structure, characterized in that: The invention is composed of cobalt core-shell structured nitrogen-doped porous carbon Co-NC-1 / NC-2 and Ru nanoparticles, wherein the nitrogen source of RuCo-NC-1 / NC-2 is dimethylimidazole and terephthalic acid organic ligand, the cobalt source is hexahydrated cobalt nitrate, and the ruthenium source is ruthenium trichloride hydrate; wherein, The Co-NC-1 / NC-2 is prepared by calcining ZIF-67 / MOF-74 at high temperature, wherein the Co metal ions are reduced in a hydrogen-argon mixed gas calcination atmosphere; The ZIF-67 / MOF-74 is obtained by chemical synthesis using cobalt nitrate hexahydrate, dimethylimidazole and terephthalic acid organic ligand as raw materials; The ruthenium nanoparticles are obtained by reducing ruthenium trichloride hydrate with ammonia borane.
2. The nitrogen-doped porous carbon composite material with a ruthenium-cobalt bimetallic core-shell structure according to claim 1, characterized in that: ZIF-67 has a rhombic dodecahedral structure and a size of 0.88 μm; ZIF-67 / MOF-74 presents a rough-surfaced rhombic dodecahedron structure with a size of 1.15 μm; Co-NC-1 / NC-2 presents an inwardly concave rhombic dodecahedron structure with a size of 1.05 μm and a coating layer thickness of 42 nm; RuCo-NC-1 / NC-2 presents an inwardly concave rhombic dodecahedron structure with a size of 1.05 μm and a coating thickness of 42 nm; Ru nanoparticles are loaded in the internal pores of Co-NC-1 / NC-2.
3. A method for preparing nitrogen-doped porous carbon loaded with ruthenium-cobalt bimetallic core-shell structure, characterized in that The following steps are involved: Step 1, preparation of ZIF-67, first, under certain conditions, cobalt nitrate hexahydrate is placed in methanol for ultrasonication to obtain solution A; at the same time, dimethylimidazole is placed in methanol to obtain solution B; then, under magnetic stirring conditions, solution B is slowly added dropwise to solution A and mixed evenly to obtain solution C; then, at room temperature, solution C is reacted under conditions of ultrasonication followed by stirring; after the reaction is completed, the purple precipitate obtained by the reaction is centrifuged and washed under certain conditions; finally, it is dried under certain conditions to obtain purple precipitate ZIF-67; Step 2, preparation of ZIF-67 / MOF-74, first, ZIF-67, cobalt nitrate hexahydrate and terephthalic acid obtained in step 1 are placed in a DMF solution and mixed to obtain a solution D, then, under certain conditions, the solution D is subjected to a hydrothermal reaction, after the reaction is completed, the precipitate obtained by the reaction is centrifuged and washed under certain conditions; finally, it is dried under certain conditions to obtain a dark red precipitate ZIF-67 / MOF-74; Step 3, preparation of Co-NC-1 / NC-2, calcining the ZIF-67 / MOF-74 obtained in step 2 under certain conditions to obtain nitrogen-doped porous carbon Co-NC-1 / NC-2 with a cobalt core-shell structure; Step 4, preparation of RuCo-NC-1 / NC-2, first, Co-NC-1 / NC-2 and ruthenium trichloride hydrate satisfy a certain mass ratio, Co-NC-1 / NC-2 is placed in deionized water to obtain solution E, and at the same time, ruthenium trichloride hydrate is placed in deionized water to obtain solution F, then, under magnetic stirring conditions, solution F is slowly added dropwise to solution E and mixed evenly to obtain solution G, and then solution G is reacted at room temperature under the conditions of first ultrasound and then stirring. After the reaction is completed, deionized water is used as a washing liquid, and the purple precipitate obtained by the reaction is filtered and washed, and finally, it is dried under certain conditions to obtain a black product loaded with ruthenium cobalt bimetallic core-shell structure nitrogen-doped porous carbon RuCo-NC-1 / NC-2.
4. The preparation method according to claim 3, characterized in that: In the step 1, the molar ratio of cobalt nitrate hexahydrate to dimethylimidazole is 1:4; In the step 2, the mass ratio of ZIF-67, cobalt nitrate hexahydrate, and terephthalic acid is 10:3:1; In step 3, the volume ratio of hydrogen to argon in the hydrogen-argon mixed gas is 1:19; In the step 4, the mass ratio of Co-NC-1 / NC-2 to ruthenium trichloride hydrate is 10:
3.
5. The preparation method according to claim 3, characterized in that: In the step 1, the ultrasonic condition for preparing solution A is that the ultrasonic time is 5-10 min; In step 1, the conditions of ultrasonication followed by stirring are as follows: the ultrasonication time is 5-10 min, and the stirring time is 4-6 h; In step 1, the centrifugal washing conditions are: methanol is used as the washing liquid, and the centrifugal speed is 6000-8000 r·min -1 The centrifugation time is 3-5 minutes, and the washing times are 3-5 times; the drying conditions are as follows: the drying temperature is 60-80°C, and the drying time is 10-12 hours.
6. The preparation method according to claim 3, characterized in that: In step 2, the conditions of the hydrothermal reaction are: the hydrothermal temperature is 100-120° C., and the hydrothermal time is 3-5 h; In step 2, the centrifugal washing conditions are: ethanol as the washing liquid, and the centrifugal speed is 6000-8000 r·min -1 The centrifugation time is 3-5 minutes, and the washing times are 3-5 times; the drying conditions are as follows: the drying temperature is 60-80°C, and the drying time is 10-12 hours.
7. The preparation method according to claim 3, characterized in that: In step 3, the calcination conditions are: argon-hydrogen mixed atmosphere, heating rate 3-5°C·min -1 , calcination temperature 450-650℃, calcination time 2-4h.
8. The preparation method according to claim 3, characterized in that: In step 4, the conditions of ultrasonication followed by stirring are as follows: the ultrasonication time is 20-40 min, and the stirring time is 20-30 min; In step 4, the drying conditions are as follows: the drying temperature is 60-80° C. and the drying time is 10-12 hours.
9. The nitrogen-doped porous carbon loaded with ruthenium-cobalt bimetallic core-shell structure according to claim 1, characterized in that: When used as a catalyst for the hydrolysis and hydrogenation reaction of ammonia borane, at a temperature of 25°C, the hydrolysis rate is 98-100%, the time for complete hydrogenation is 15-40s, and the maximum hydrogenation conversion rate is 400-450mol H2 ·mol Ru -1 ·min -1 ; The activation energy of catalytic hydrogen release is E a =25-30 kJ·mol -1 .
10. The nitrogen-doped porous carbon loaded with ruthenium-cobalt bimetallic core-shell structure according to claim 1, characterized in that: When used as a catalyst for the hydrolysis and hydrogenation reaction of ammonia borane at 25°C, the hydrolysis rate remained at 100% when the number of cycles was 10, and the time for complete hydrogenation was 50s when the number of cycles was 5, and the maximum hydrogen evolution conversion rate was 365.8 mol H2 ·mol Ru -1 ·min -1 The maximum hydrogen evolution conversion rate was maintained at 89.5%; when the number of cycles was 10, the time for complete hydrogen release was 68s, and the maximum hydrogen evolution conversion rate was 289.9mol H2 ·mol Ru -1 ·min -1 , the retention rate of the maximum hydrogen evolution conversion rate is 70.9%.